High Contrast PET Imaging of Subcortical and Allocortical Amyloid-β in Early Alzheimer’s Disease Using [11C]AZD2184 - Mattsson, Patrik; Cselényi, Zsolt; Forsberg Morén, Anton; Freund-Levi, Yvonne; Wahlund, Lars-Olof; Halldin, Christer; Farde, Lars (Journal of Alzheimer's disease, 2024)
Background: Deposits of amyloid-β (Aβ) appear early in Alzheimer’s disease (AD). Objective: The aim of the present study was to compare the presence of cortical and subcortical Aβ in early AD using positron emission tomography (PET). Methods: Eight cognitively unimpaired (CU) subjects, 8 with mild cognitive impairment (MCI) and 8 with mild AD were examined with PET and [11C]AZD2184. A data driven cut-point for Aβ positivity was defined by Gaussian mixture model of isocortex binding potential (BPND) values. Results: Sixteen subjects (3 CU, 5 MCI and 8 AD) were Aβ-positive. BPND was lower in subcortical and allocortical regions compared to isocortex. Fifteen of the 16 Aβ-positive subjects displayed Aβ binding in striatum, 14 in thalamus and 10 in allocortical regions. Conclusions: Aβ deposits appear to be widespread in early AD. It cannot be excluded that deposits appear simultaneously throughout the whole brain which has implications for improved diagnostics and disease monitoring.